Pengaruh Kecanggihan Teknologi Informasi, Partisipasi Manajemen, Dan Kemampuan Teknik Pemakai Sistem Informasi Akuntansi Pada Kinerja Individu Pada Perusahaan Batik Brotoseno Sragen - Saifulloh, Muhammad, Drs. Agus Endro Swarno, Msi (2016)
The purpose of this study to Know Effect of sophistication of Information Technology, Participation and Capabilities Management Accounting Information Systems Engineering User to Individual Performance. The research method used survey method. In this case the researchers spread to textile companies in Sragen. The sample in this study is that company employees at the offices that use computers in Sragen regency as many as 67 employees. The sampling technique used purposive non-random sampling is a sampling technique with certain pertimbanga. The analytical tool used: 1) Test Validity, 2) Test Reliability, 3) Classical Assumption Test, 4) Test Linear Regression, 5) Test t, 6) F Test (Test Accuracy Model) and 7) The coefficient of determination (R2). The results of the analysis as follows: 1) There is the influence of sophistication of Information Technology on individual performance, 2) There is a Management Participation influence on the performance of individuals, 3) influences of Engineering Capabilities User Accounting Information Systems on the performance of individuals.